Effects of non-pharmacological interventions on youth with internet addiction: a systematic review and meta-analysis of randomized controlled trials - Jiang, Yue-Shuai; Liu, Tian-Hong; Qin, Dan; Wang, Zi-Pu; He, Xiao-Ya; Chen, Yan-Nan (Frontiers in Psychiatry, 2024)
Objective: To assess the overall effectiveness of non-pharmacological interventions on internet addiction (IA) in youth. Method: Randomized controlled trials (RCTs) published from their inception to April 1, 2023 were searched in Cochrane, Embase, Medline, Web of Science, China National Knowledge Infrastructure, China Science and Technology Journal Database, Chinese BioMedical Literature Database, and WanFang Data. Two reviewers independently extracted data and evaluated bias using the Cochrane Risk of Bias tool. Results: Sixty-six studies performed from 2007 to 2023, with a total of 4,385 participants, were identified. The NPIs included group counseling, cognitive behavioral therapy, sports intervention, combined interventions, eHealth, educational intervention, positive psychology intervention, sand play intervention, and electrotherapy. The results revealed that NPIs significantly reduced IA levels (standardized mean difference, SMD: -2.01, 95% confidence interval, CI: -2.29 to -1.73, I²= 93.0%), anxiety levels (SMD: -1.07, 95%CI:-1.41 to -0.73, I²= 72.4%), depression levels (SMD: -1.11, 95%CI: -1.52 to -0.7, I²= 84.3%), and SCL-90 (SMD: -0.75, 95%CI: -0.97 to -0.54, I²= 27.7%). Subgroup analysis stratified by intervention measure showed that cognitive behavioral therapy, group counseling, sports intervention, combined intervention, educational intervention, positive psychology intervention, sandplay intervention, and mobile health were all effective in relieving symptoms of IA except electrotherapy.NPIs appear to be effective in the treatment of IA in youth, which would act as an alternative treatment of IA. Further studies with larger sample sizes and robust designs are needed.